An Evaluation of the National Interactive Kindergarten Curriculum, the Document of the General Framework and the General and Specific Outcomes for the Kindergarten Curriculum of Children with Hearing Impairments from Their Teachers' Perspectives: A Qualit - Al-Zboon, Eman (Jordan Journal of Educational Sciences, 2015)
This study aimed to evaluate the national interactive kindergarten curriculum and the document of the general framework and the general and specific outcomes for the kindergarten curriculum of children with hearing impairments from their teachers' perspectives during the academic year (2014/2015). The sample of the study consisted of all the kindergarten teachers working with children with hearing impairments in Amman and Zarqa (14 teachers). To collect the data, the researcher used qualitative methodology by using a semi-structured interview method and then the resulting data were analyzed using content analysis. The results revealed that the national interactive curriculum for kindergarten is inappropriate, and there is a need for the development of a special curriculum for children with hearing impairments. The findings also showed some suggested amendments to the curriculum to be more appropriate for children with hearing impairments. Finally, the results indicated that the general framework and general and specific outcomes for the kindergarten curriculum of children with hearing impairments are appropriate for children with hearing impairments. The study proposed a set of recommendations according to the findings of the study, mainly involving the development of a professional team to review the curriculum for children with hearing impairments as well as reviewing the general framework and general and specific outcomes for children with hearing impairments, and to implement required amendments